Acute necrotizing eosinophilic myocarditis as a manifestation of DRESS caused by cephalexin during pregnancy. (8th October 2020) - Machnikowski, N.; Alani, A.; Douglas, H.; Houghton, J.; Herron, B.; Hoey, S.; Johnston, P.
Abstract : Click here for the corresponding questions to this CME article.